Legal Fundamentals of Healthcare Law - Jackman, Tiffany (Open textbook library., 2024)
Healthcare, a field dedicated to the well-being of individuals and communities, operates within an intricate web of legal principles. Understanding these laws is not simply a professional necessity for doctors, nurses, administrators, and researchers; it’s also an ethical imperative for anyone who interacts with the healthcare system. This book is your compass, guiding you through the labyrinth of legal fundamentals that shape the landscape of healthcare.